2019
DOI: 10.3390/su11041160
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Accessibility to Hospitals Based on Web Mapping API: An Empirical Study in Kaifeng, China

Abstract: The accessibility of hospital facilities is of great importance not only for maintaining social stability, but also for protecting the basic human right to health care. Traditional accessibility research often lacks consideration of the dynamic changes in transport costs and does not reflect the actual travel time of urban residents, which is critical to time-sensitive hospital services. To avoid these defects, this study considered the city of Kaifeng, China, as an empirical case, and directly acquired travel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…The value of was between 1 and 2. According to results of other papers, we considered the impact of the attractiveness of secondary medical service to be greater than the effect of distance [ 28 , 29 ], and distance attenuation is low, so the value of was set to 1; d 0 is the space-time threshold. Because the study area is a provincial area with a large spatial range, it is more difficult for residents in remote areas to obtain medical resources than it is for residents in urban areas.…”
Section: Methodsmentioning
confidence: 99%
“…The value of was between 1 and 2. According to results of other papers, we considered the impact of the attractiveness of secondary medical service to be greater than the effect of distance [ 28 , 29 ], and distance attenuation is low, so the value of was set to 1; d 0 is the space-time threshold. Because the study area is a provincial area with a large spatial range, it is more difficult for residents in remote areas to obtain medical resources than it is for residents in urban areas.…”
Section: Methodsmentioning
confidence: 99%
“…Results indicated that geo-located data can provide more accurate and realistic information than static or partially dynamic analyses. Zheng et al (2019) considered the dynamic changes in transport costs to hospital services using public transit and self-driving modes of transportation. Instant TTs to access hospital services were considered at the peak and off-peak traffic hours of the day.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Health and social services are attributed to the government component as government agencies are in most countries accountable for those services. The accessibility of hospitals is of particularly high importance that requires an extensive data driven analysis to consider dynamic changes in transport costs and travel time in order to provide universal access to hospital services for the whole population [226].…”
Section: Smart Healthmentioning
confidence: 99%